ECOLOGICAL CITIZENSHIP PADA MASYARAKAT PERKOTAAN STUDI TENTANG PEDULI LINGKUNGAN DI KELURAHAN JAMBANGAN SURABAYA - Alvianto, Muchamad Bagas; Harmanto, Harmanto (Kajian Moral dan Kewarganegaraan, 2025)
Environmental problems in urban areas, such as the degradation of air and water quality and poor waste management, which are largely caused by low ecological awareness among citizens. This study aims to describe the practice of Ecological Citizenship in urban communities, particularly RW 3 and RT 5 in Jambangan Subdistrict, Surabaya. A qualitative approach with a case study method was employed. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The study is based on two main theoretical frameworks: Andrew Dobson’s Ecological Citizenship and the Social Construction Theory of Peter L. Berger & Thomas Luckmann. The findings indicate that residents of Jambangan actively shape and practice ecological awareness through habitual behaviors and participation in environmental programs such as waste banks, urban farming, and integrated wastewater management. These practices are socially constructed through interaction local cultural values of mutual cooperation, and community participation. This research emphasizes the importance of integrating civic awareness and ecological responsibility as a foundation for sustainable environmental development.